Early Response of Antimicrobial Resistance and Virulence Genes Expression in Classical, Hypervirulent, and Hybrid hvKp-MDR Klebsiella pneumoniae on Antimicrobial Stress - Anastasiia D. Fursova; Mikhail V. Fursov; Evgenii I. Astashkin; Tatiana S. Novikova; Galina N. Fedyukina; Angelina A. Kislichkina; Irina A. Alexandrova; Olga N. Ershova; Ivan A. Dyatlov; Nadezhda K. Fursova (Antibiotics, 2021)
Klebsiella pneumoniae is an increasingly important hospital pathogen. Classical K. pneumoniae (cKp) and hypervirulent K. pneumoniae (hvKp) are two distinct evolutionary genetic lines. The recently ongoing evolution of K. pneumoniae resulted in the generation of hybrid hvKP-MDR strains. K. pneumoniae distinct isolates (n = 70) belonged to 20 sequence types with the prevalence of ST395 (27.1%), ST23 (18.6%), ST147 (15.7%), and ST86 (7.1%), and 17 capsular types with the predominance of K2 (31.4%), K57 (18.6%), K64 (10.0%), K1 (5.7%) were isolated from patients of the Moscow neurosurgery ICU in 2014–2019. The rate of multi-drug resistant (MDR) and carbapenem-resistant phenotypes were 84.3% and 45.7%, respectively. Whole-genome sequencing of five selected strains belonging to cKp (ST395K47 and ST147K64), hvKp (ST86K2), and hvKp-MDR (ST23K1 and ST23K57) revealed blaSHV, blaTEM, blaCTX, blaOXA-48, and blaNDM beta-lactamase genes; acr, oqx, kpn, kde, and kex efflux genes; and K. pneumoniae virulence genes. Selective pressure of 100 mg/L ampicillin or 10 mg/L ceftriaxone induced changes of expression levels for named genes in the strains belonging to cKp, hvKp, and hybrid hvKp-MDR. Obtained results seem to be important for epidemiologists and clinicians for enhancing knowledge about hospital pathogens.